Development of Learning Device Based on 21st Century Skill with Implementation of Problem Based Learning to Increase Critical Thinking Skill of Students on Polyhedron for Grade 8th Junior High School - Melva Yola Afdareza; Putri Yuanita; Maimunah Maimunah (Journal of Educational Sciences, 2020)
This research aims is to produce a learning device based on 21st century skills with the implementation of problem-based learning to increase the critical thinking skill of students on polyhedron for grade 8th junior high school. The type of this research is development research using Plomp’s model, there are (1) preliminary research phase; (2) the prototype phase; and (3) assessment phase. The results of this research are a learning device based on 21st century skill with the implementation of  problem-based learning to increase the critical thinking skill of students on polyhedron for grade 8th junior high school. The results of the syllabus, RPP, LKPD validation and critical thinking skills show valid and very valid criteria with values of 3.19; 3.32; 3.26; and 3.13. In the final product test phase, learning devices were used through pre-experimental research to see the increase in critical thinking skills and there was an increase in the critical thinking skill of students using learning devices. This means that the learning device based on 21st century skill with the implementation of problem-based learning to increase the critical thinking skill of students on polyhedron for grade 8th junior high school has been valid, practical, and effective.